Manajemen Kelas Berbasis Pemisahan Gender dan Relasinya dengan Prestasi Siswa: Studi Kasus di MTs Darullughah Wadda’wah - Zainal Abidin; Asep Rahmatullah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
Research on gender segregation-based classroom management and its relation to student achievement at Mts Darullughah Wadda'wah is motivated by the assumption that gender-segregated classes in several schools with religious backgrounds are thought to reduce student achievement. This research uses qualitative methods with a case study design. This research concludes that the Gender Separation Management carried out at Mts Dalwa which is under the auspices of the Dalwa Islamic Boarding School is based on theological and psychological principles. In terms of theology, it is more about being careful so that there are no khtilats that have the potential to lead to wider immorality. Psychologically, the gender separation management at Mts Dalwa believes that men and women have slightly different learning potential. In general, men grow up in a competitive spirit while women thrive in an atmosphere of togetherness. Gender separation management in relation to student achievement also has a positive trend. This is proven by the quite good grades and the students' morals towards asatizah are also relatively good.